GOOD LAW AND POLICY-MAKING: A PREREQUISITE FOR COMPETITIVE INNOVATION STRATEGIES? - Stankevice, Inga; Matijosaitiene, Irina (European Scientific Journal, ESJ, 2015)
The contemporary environment requires policy-makers to act responsible. However, in existing literature, there is no explicit agreement on which aspects of institutional environment, including common law are more important than others for a country’s prosperity, economic growth, entrepreneurship, or innovativeness. Therefore, the paper aims to reveal whether fair, transparent and effective policy-making fosters the emergence of competitive strategies for innovation, or instead limits the range of commonly-acceptable means of fair and legal competition. The empirical research covers 60 innovation variables across 127.674 organizations, 12 core and 19 additional industrial sectors, 16 European economies and 368 institutional variables, thus pointing to the impressive scope of the research. What makes the paper original is its focus on the responsible policy-making as a contributor to competitive practices for innovation.